Unmanned aerial vehicle search of unknown region with limited endurance - Chan, Jonathan Wei-Jie (2017)
The purpose of this report is to document the design and implementation of a search region and exploration algorithm for an Unmanned Aerial Vehicle (UAV). The algorithm seeks to allow the UAV to map and traverse an unknown region to gather as much information as possible, whilst considering constraints in limited endurance and sensor reading. Due to the limited endurance, the UAV needs to return to the base for refuelling. This project is split into 2 sections. The first section requires the author to discretize the search region and to initialize it, while the second section requires the author to come up with algorithm for the UAV to traverse the search region and to map it out. Both sections were completed, and the algorithm was implemented successfully.